Between Heaven and Hell: Experiences of Preoperative Pain and Pain Management among Older Patients with Hip Fracture - Anna Unneby RN, MSc; Yngve Gustafson MD, PhD; Birgitta Olofsson RN, PhD; Britt-Marie Lindgren RN, PhD (SAGE Publishing, 2022)
Introduction Among older adults, hip fracture is a common and serious consequence of a fall. Preoperative pain is common and often severe among patients with hip fracture. Opioids are usually used but have many side effects. One alternative is a femoral nerve block, which has been shown to reduce pain and lower the need for opioids. However, to our knowledge no study has explored qualitatively how patients with hip fracture experience treatment with femoral nerve block. Objective The aim of this study was to explore experiences of preoperative pain and pain management among older patients with hip fracture who had received a femoral nerve block. Method A qualitative design with semi-structured interviews (n = 23) conducted 2-6 days after surgery. Inclusion criteria were Swedish-speaking patients aged 70 years or older with hip fracture admitted to the orthopedic ward, treated with femoral nerve block before nursing actions. Data were analyzed with qualitative content analysis. Results Our result revealed one theme, hovering between heaven and hell, with five subthemes: how the pain was described - no pain, to worst pain and everything in between; they were dealing with pain in their own way; felt dependent on staff´s willingness to relieve pain; pain management could be lifesaving and a near-death experience; and how they experienced memory loss with respect to the pain and pain management. Conclusion The experience of pain and pain management was described as hovering between heaven and hell. We conclude that independent of which pain management given, staff should have an individualized pain mangement approach towards the patient in order to achieve well managed pain.